Wrist abscess due to drug-resistant Pasteurella multocida. (2021) - Wei, Abraham; Dhaduk, Nehal; Taha, Basil
Abstract: Many cases of cat and dog bites are associated with Pasteurella spp. infections. Antimicrobial therapy usually entails a β-lactam-β-lactamase inhibitor combination such as amoxicillin-clavulanic acid. Drug resistance in human Pasteurella spp. infections has rarely been reported in literature. In this report, we introduce the first documented case of a human Pasteurella spp. infection with resistance to amoxicillin-clavulanic acid. The potential emergence of drug-resistant Pasteurella spp may alter our therapeutic approach to animal bites in the future. This case highlights the need for further epidemiologic studies on Pasteurella spp antibiotic susceptibility patterns in both humans and cats.